PEMIDANAAN CYBERCRIME DALAM PERSPEKTIF HUKUM PIDANA POSITIF - Andri Winjaya Laksana (Unissula, 2019)
Cybercrime is a crime that uses computers as a tool and crimes that target computers. With the enactment of Law Number 11 of 2008, which includes and regulates everything about cybercrime, it has made it easier for efforts to combat cybercrime in Indonesia. In this Law, imprisonment is still dominant in imposing crimes against cybercriminals. Due to the characteristics of cybercrime perpetrators that are unique and different from the characteristics of conventional criminals, including perpetrators who are relatively young, educated, respectable people, skilled in operating computers and their application programs like technological, creative, and resilient challenges, it is necessary to deal with them separately. which is different from other criminal offenders. This is based on the concept of individualization of punishment, that the crime must be in accordance with the convict's condition by observing the principle of mono dualistic balance. Supervision punishment, or social work punishment, and criminal fines, compensation, and certain actions can be used as an alternative to short-term imprisonment against cybercrime offenders.